Library automation - Singh, Pramod Kumar (Shree, 2005)
Contents of material: 1/ Introduction to automated libraries. 2/ Automation in public libraries. 3/ Virtual reference services. 4/ Access management and securty. 5/ Storing textual materials. 6/ Competencies for information professionals. 7/ Information retrieval and descriptive matadata. 8/ Internet and the World Wide Web. 9/ Electronic publishing. 10/ Economic and legal issues.